Some geographical aspects of water supply in Southwest England during the 1975-6 drought - Gardiner, V. (ERDKUNDE, 1981)
Even in years with sufficient rainfall, water supply in South West England is not without problems. These problems were particularly acute in 1976, partly because of the extreme climatic conditions, and partly because of the insufficient time available to the newly formed South West Water Authority to implement a regional water management strategy. The severity of drought intensified generally eastward, and this drought grading gradient corresponds overall to water supply shortages. Actual water consumption for 1976 is mapped as a proportion of projected demand and some of the underlying dependencies of the resulting distribution pattern are discussed. The administration's response to the drought is outlined. It appears that the spatial pattern of water supply depends on both human and natural factors and that a regional water management policy in South West England would be needed.